Poultry disease occurrences and their impacts in Ethiopia - Asfaw, Yohannes T.; Ameni, G.; Medhin, G.; Gumi, B.; Hagos, Y.; Wieland, Barbara (Springer, 2021)
Poultry production contributes significantly to the livelihoods of Ethiopian farmers and to the national economy although it is hampered by different factors, including poultry diseases. There is scarcity of published evidences on the occurrence and impacts of poultry diseases although such evidences are important for policy makers in designing appropriate interventions. A total of 595 households were interviewed and 11 FGDs were conducted to collect data on the occurrence of diseases and the number of dead chickens in the last 12 months. Hence, respiratory diseases, sudden death, and eye-face-head diseases were mentioned in all of the FGDs as the most frequently occurring disease in the districts. Of households interviewed, 86.1% reported poultry disease occurrence in the last 12 months, and gastrointestinal, eye-face-head, and neurological diseases were identified to be the top three ranked diseases of chickens in the districts. Flocks with access to diagnostic services (Adj. OR = 4.16; P = 0.004) and/or access to animal health providers (Adj. OR = 10.50; P = 0.001) were more likely to report disease occurrence. In the studied population, the diseases resulted in deaths of 2219 chickens valued at 352,219.5 Birr (11,740.65 USD) and a mean crude mortality of 31.87%. Female-lead households (mean difference = 5.95%; P = 0.018) and multiple age units present on the farm (mean difference = 20.92%; P = < 0.000) had higher chicken mortality. Similarly, higher mortality was reported in flocks without access to diagnosis (mean difference = 9.97%; P = < 0.000) and vaccination (mean difference = 12.34%; P = < 0.000) services. The high occurrence of disease and mortalities might be explained by a lack of an organized poultry health service delivery system in the country. Therefore, a carefully designed health service delivery system addressing needs of poultry producers, supported by relevant policy and corresponding strategies, is recommended to address the indicated challenges. Moreover, private health providers with well-defined roles need to be engaged to successfully and sustainably solve the poultry disease problems.